Contribution of root system architecture and function in the performance of tropical maize (Zea mays L.) genotypes under different moisture regimes - Zaidi, Pervez Haider; Seetharam, Kaliyamoorthy; Vinayan, Madhumal Thayil; Rashid, Zerka; Krishnamurthy, Lakshmanan; Vivek, Bindiganavile Sampath (Southern Cross Publishing, 2022)
Understanding how roots respond to increasing rate of evapotranspiration in warmer days and exposure to dry spells is crucial for saving productivity of rainfed crops, including maize, grown in Asian tropics. In a semi-automatic root phenotyping facility (lysimetric system) a set of 100 elite and diverse tropical maize inbred lines were phenotyped under managed drought stress (DT) and well-watered (WW) conditions. Plants were grown in PVC (Polyvinyl chloride) cylinder of 30.0 cm diameter and 150.0 cm length. In drought experiment, last irrigation was applied based accumulated growing degree days (∑GDD) criteria to achieved reproductive stress DT, whereas optimal moisture was maintained in WW trials. Data recorded on various root structural and function traits in both DT and WW trials. Significant phenotypic variability was observed for various root traits, including both structural and functional traits, under both the moisture regimes. Correlation studies showed that grain yield of early maturity group of genotypes was positively and significantly associated with all the root structural traits under drought, whereas, in case of medium and late maturity group of entries root structural traits showed either weak positive or significant negative correlation with grain yield under drought. Though, root functional traits of all the maturity group of genotypes showed positive and significant correlations with both grain yield and total biomass under both well-watered drought stress. Regression analysis showed that water uptake had significant positive relationship with total biomass in all the three-maturity group of genotypes. However, grain yield seems to be less dependent directly on the total amount of water uptake. We conclude that contribution of various traits in root system architecture under drought or well-watered conditions vary with maturity of genotypes. However, root functional traits, such as water uptake and transpiration efficiency are equally important across maturity groups and water availability regimes.